Pelatihan Keterampilan Takmir Masjid : Penyusunan Laporan Keuangan Masjid Desa Berdasarkan ISAK 35 - Emylia Yuniarti; Rela Sari; Imelda; Muhammad Teguh; Muhammad Subardin (Sriwijaya Accounting Community Services, 2026)
Mosque financial reporting that is managed simply can affect the low accountability of mosque management, this is due to the lack of understanding and skills of mosque administrators in presenting good financial information. The purpose of this service is to improve skills to the community through training and mentoring mosque administrators in preparing professional and accountable village mosque financial reports based on Interpretation of Financial Accounting Standards (ISAK) 35. The method of implementation uses a participatory training with an empowerment model in the form of materials and assistance in preparing financial reports for the Masjid Istiqomah management in Desa Ulak Kembahang II. The result of this service is an increase in the understanding and skills of mosque administrators in compiling mosque financial reports according to ISAK 35 standards for non-profit entities. In addition, the management has also been able to produce double entry efficiently and effectively through excel. The increase in these skills can have an impact on accountable mosque financial statement information so that public confidence also increases.